Primary Bilateral Non-Hodgkin's Lymphoma of the Adrenal Gland Presenting as Incidental Adrenal Masses. (22nd November 2015) - Rizzo, Christopher; Camilleri, David James; Betts, Alexandra; Gatt, Andre'; Fava, Stephen
Abstract : Although lymphoma may occasionally involve the adrenal glands as part of a generalized disease process, primary adrenal lymphoma (PAL) is a rare disease. We present a case of a 62-year-old woman with a history of mild/moderate hereditary spherocytosis with a well-compensated baseline haemoglobin, who presented with rapidly progressive symptomatic anaemia. During the diagnostic workup, imaging revealed bilateral large adrenal masses and she was later diagnosed with diffuse large B-cell non-Hodgkin's lymphoma (DLBCL), with the adrenal glands being the dominant site of the disease. The patient was started on systemic chemotherapy, but her disease progressed with neurological involvement which responded to second-line therapy. Her adrenal disease however was refractory to further therapy.